EFFECTIVENESS OF INTRATHECAL DEXMEDETOMIDINE IN COMBINATION WITH HYPERBARIC BUPIVACAINE FOR LOWER ABDOMINAL SURGERIES AND ITS POSTOPERATIVE ANALGESIC CHARACTERISTIC - Alam, Syed Sajjad; Nighat Abbas ,; Ali Asgher,; Muhammad Rafique ,; Anees-ur-Rehman ,; Khadijah Abid, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Intra-thecal anaesthesia is the commonly preferred, block for surgeries of lower abdomen, perineal and lower limb. It is easy to administer and very economical but needs skills. Intrathecal use of local anaesthetics possesses a short duration of action and needs early use of rescue analgesia postoperatively. Objective was to assess the efficacy of Dexmedetomidine in adjuvant with bupivacaine for neuraxial anesthesia and postoperative analgesic characteristics. It was a prospective comparative study, conducted at Anesthesia Department, Liaquat National Hospital, Karachi from January to July 2020. Methods: Overall 100 patients conveniently recruited who underwent lower abdominal procedures were allocated into two groups' by randomization, i.e., 50 in each group and were labeled as Group N and Group D10. Group N consist of 0.5% bupivacaine 10 mg (2 ml) + diluted with 0.5ml normal saline dilution and group D10 consist of 10Î¼g Dexmedetomidine + 0.5% bupivacaine 10 mg (2ml) with 0.5 ml normal saline dilution, total 2.5 ml dose in each group. The duration of block and regression was evaluated. Results: The study showed significant differences in sensory and motor block to reach T10 and Bromage 3 respectively. Patients who were assigned in Group D reported short onset of sensory to reach T10 (5.4±1.17) and motor to reach Bromage 3 (10.4±1.03) as compared to Group N (9.9±2.12 and 17±22) respectively. Participants of Group D required rescue analgesia in less amount throughout intervals as compare to group N. Conclusion: The usage of 10ug Dexmedetomidine adjuvant with 0.5% bupivacaine significantly reduced the onset on sensory T10 and motor Bromage 3 and also prolong duration of sensory and motor regression, moreover minimal adverse effects and less use of rescue analgesic drugs were observed.